Application of DFT and experimental tests for the study of compost formation between chitosan-1,3-dichloroketone with uses for the removal of heavy metals in wastewater (2025)
The environment presently contains greater amounts of heavy metals due to human activities, causing toxicity, mutagenicity, and carcinogenicity. This study evaluated a chitosan (CS) composite material combined with 1,3-dichlorocetone to extract heavy metals from affected waters, integrating experimental and computational analyses. The synthesis of chitosan, obtained from shrimp waste chitin, reached a yield of 85%. FTIR analysis confirmed key functional groups (NH2 and OH), and XRD showed high crystallinity with peaks at 2θ = 8° and 20°. The physicochemical properties evaluated included a moisture content of 7.3%, ash content of 2.4%, and a deacetylation degree of 73%, consistent with commercial standards. Chitosan exhibited significant solubility in 1.5% acetic acid, moderate solubility in water, and insolubility in NaOH, demonstrating its versatility for environmental applications. In adsorption tests, heavy metal concentrations were reduced by CS derivatives, with Cr and Pb dropping to 0.03 mg/L, and Cu and Zn to less than 0.05 mg/L. CS cross-linked with 1,3-dichlorocetone proved the most efficient, outperforming other derivatives such as glutaraldehyde and epichlorohydrin. Computational analysis evaluated key molecular interactions using DFT and the B3LYP/LANLD2Z method. The band gap energies (HOMO–LUMO) decreased to 0.09753 eV for Zn and 0.01485 eV for Pb, indicating high affinity, while Cd showed lower interaction (0.11076 eV). The total dipole moment increased remarkably for Zn (14.693 Debye) and Pb (7.449 Debye), in contrast to Cd (4.515 Debye). Other descriptors, such as chemical hardness (η), reflected a higher reactivity for Zn (0.04877 eV) and Pb (0.00743 eV), which favors adsorption. The correlation between experimental and computational results validates the efficiency and selectivity of CS/1,3-dichlorocetone for removing heavy metals, especially Pb and Zn. This material stands out for its adsorbent capacity, sustainability, and economic viability, positioning it as a promising solution for wastewater remediation.